Compact With The Charter And Laws Of The Colony Of New Plymouth 184 (1836) - (:unkn) unknown (My University, 1677)
"It is enacted by the Court That the order made by the Generall ing to thecarry Court October the fourth 1675 respecting carrying of armes to the Meeting be put in execution by all such psons as are by the Lawes of this Collonie required to beare armes viz : the one halfe of the Companie one day and the other the other day and soe continewed untill further order to Contrary from the Govr or Councell."
Keywords: REQUIRED CARRY